Hana dan Pergulatan Perempuan Modern: Antara Harapan, Luka, dan Iman - Nome, Obria Mi’a; Zay, Yudika Niat; Bambangan, Malik (Pusat Riset dan Inovasi Nasional, 2025)
Modern women face layered complexities of challenges in navigating life in the contemporary era. Through an in-depth analysis of the character Hana as a representation of contemporary women, this article explores the dynamics of internal struggles encompassing aspects of hope, psychological trauma, and the search for spiritual meaning. This study uses a descriptive qualitative approach with narrative analysis to understand the psychosocial phenomena experienced by urban Indonesian women. The research results show that modern women experience a continuous dilemma between social expectations, personal aspirations, and spiritual needs, which is reflected in the life journey of the character Hana. These findings make an important contribution to understanding the construction of Indonesian women's identity in the 21st century.